Determinants Of ROA In Sharia Banks: The Role Of NPF, FDR, And Net Imbalance On Profitability - Zulkarnain, Muhammad; Ridwan Effendi; Marti Utari (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
Islamic banks as a company still have a goal of profit, where profit is often used as a measure of the company's performance. One of the profit ratios is the return on assets (ROA) ratio. Then the ROA in the previous study was influenced by many factors, while in this study it was seen based on the net performance financing (NPF) ratio, financing to deposit ratio (FDR), and net return (NI). The purpose of the study was to determine the effect of the NPF ratio, FDR ratio, and NI ratio on the ROA ratio. The research population was Islamic banks listed on the Indonesia Stock Exchange (IDX), namely 4 companies with data from the first-fourth quarter of 2021 to the second quarter of 2024. Panel data regression data analysis techniques. The results of the study showed that simultaneously net performance financing (NPF), financing to deposit ratio (FDR), and net return (NI) were significant on the return on assets (ROA) ratio, but partially net performance financing (NPF) did not affect the return on assets (ROA) ratio while financing to deposit ratio (FDR) and net return (NI) were significant on the return on assets (ROA) ratio.